Risk Factors and Outcomes for Patients with Bloodstream Infection Due to Acinetobacter baumannii-calcoaceticus Complex - Chopra, Teena (American Society for Microbiology, 2014)
Identifying patients at risk for bloodstream infection (BSI) due to Acinetobacter baumannii-Acinetobacter calcoaceticus complex (ABC) and providing early appropriate therapy are critical for improving patient outcomes. A retrospective matched case-control study was conducted to investigate the risk factors for BSI due to ABC in patients admitted to the Detroit Medical Center (DMC) between January 2006 and April 2009. The cases were patients with BSI due to ABC; the controls were patients not infected with ABC. Potential risk factors were collected 30 days prior to the ABC-positive culture date for the cases and 30 days prior to admission for the controls. A total of 245 case patients were matched with 245 control patients. Independent risk factors associated with BSI due to ABC included a Charlson's comorbidity score of ≥3 (odds ratio [OR], 2.34; P = 0.001), a direct admission from another health care facility (OR, 4.63; P < 0.0001), a prior hospitalization (OR, 3.11; P < 0.0001), the presence of an indwelling central venous line (OR, 2.75; P = 0.011), the receipt of total parenteral nutrition (OR, 21.2; P < 0.0001), the prior receipt of β-lactams (OR, 3.58; P < 0.0001), the prior receipt of carbapenems (OR, 3.18; P = 0.006), and the prior receipt of chemotherapy (OR, 15.42; P < 0.0001). The median time from the ABC-positive culture date to the initiation of the appropriate antimicrobial therapy was 2 days (interquartile range [IQR], 1 to 3 days). The in-hospital mortality rate was significantly higher among case patients than among control patients (OR, 3.40; P < 0.0001). BSIs due to ABC are more common among critically ill and debilitated institutionalized patients, who are heavily exposed to health care settings and invasive devices.